Utilization of Organic Waste into Liquid Organic Fertilizer in Karang Anyar Palembang City - Marlina, Neni; Aryani, Ida; Marlina, Marlina; Asmawati, Asmawati; Khodijah, Khodijah; Aminah, Iin Siti; Hawayanti, Erni; Rosmiah, Rosmiah; Zairani, Fitri Yetty; Hasani, Burlian; Yulianto, Deny (Universitas Muhammadiyah Palembang, 2022)
Organic waste in the form of vegetable and fruit residues from the Gandus market has a high potential to be used as liquid organic fertilizer with the help of Azospirillum bacteria and phosphate solvents. The liquid organic fertilizer produced can be used as fertilizer for plants in farmers' yards and gardens and reduce environmental pollution as well as streamline the use of chemical fertilizers and its manufacture is practical and easy for the community to do. The counseling was carried out in Karang Anyar Village, Gandus District, Palembang City from February to March 2019. The method was carried out by counseling and demonstrating how to make liquid organic fertilizer with the help of Azospirillum bacteria and phosphate solvent. The community in Karang Anyar Village is very excited to receive knowledge in the utilization of organic waste into liquid organic fertilizer.